2020
DOI: 10.3389/fnhum.2020.00202
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Differences in Functional Interactions Between the Dorsal Lateral Prefrontal Cortex and Ipsilateral Motor Cortex

Abstract: Background: The dorsolateral prefrontal cortex (DLPFC) in both hemispheres have a central integrative function for motor control and behavior. Understanding the hemispheric difference between DLPFC and ipsilateral motor cortex connection in the resting-state will provide fundamental knowledge to explain the different roles DLPFC plays in motor behavior. Purpose: The current study tested the interactions between the ipsilateral DLPFC and the primary motor cortex (M1) in each hemisphere at rest. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…In contrast, rTMS with low frequency has been used to treat depression when the rTMS is applied to the right PFC. Furthermore, dorsolateral PFC (DLPFC) inhibitory effects on the ipsilateral primary motor cortex (M1) is higher in the left than in the right hemisphere [71], even though right DLPFC has inhibitory effects on the left M1 [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, rTMS with low frequency has been used to treat depression when the rTMS is applied to the right PFC. Furthermore, dorsolateral PFC (DLPFC) inhibitory effects on the ipsilateral primary motor cortex (M1) is higher in the left than in the right hemisphere [71], even though right DLPFC has inhibitory effects on the left M1 [44].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, rTMS with low frequency has been used to treat depression when the rTMS is applied to the right PFC. Furthermore, dorsolateral PFC (DLPFC) inhibitory effects on the ipsilateral primary motor cortex (M1) is higher in the left than in the right hemisphere [71], even though right DLPFC has inhibitory effects on the left M1 [44]. Right-handers present stronger effects from the left-to-right MC, which seems to involve excitatory and inhibitory inter-hemispheric activity [73], supporting the idea of an increased activity tone in right-handers’ left M1.…”
Section: Discussionmentioning
confidence: 99%
“…The left DLPFC was targeted with anodal tDCS for several interrelated reasons: (1) Several studies have shown that left DLPFC-tDCS can improve fine motor [ 10 , 11 , 15 ] and gross motor performance [ 24 , 25 , 26 ], (2) methodologies have been determined using simple measuring equipment for the accurate placement of the tDCS electrodes for DLPFC [ 27 ] without the need for expensive equipment that was unavailable at the athlete’s training facility. For instance, the need to use transcranial magnetic stimulation (TMS) to find the motor hot spot for M1-tDCS, and (3) the left DLPFC has ipsilateral connections to several brain regions, including premotor cortex, basal ganglia, cerebellum, and SMA [ 29 ], which likely partially explains its role in motor planning and motor learning processes [ 29 , 30 ] and its indirect influence on M1 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Reorganization in the contralateral SM1 appeared to be a natural consequence because it was previously reported that cortical expansion accompanies intense limb use and motor learning. 27 In contrast, although there is no direct anatomical connection between the DLPFC and M1, 42,43 DLPFC activation decreases ipsilateral M1 corticospinal excitability. 42,44 In fact, the DLPFC is known to be involved in motor control, for example, in force control 45 and motor memory maintenance, 46 which might have contributed to the task of regulating force to 20% MVC in this study.…”
Section: Reorganization In the Frontal Lobe And Visual Pathways Induced By Long-term Sports Activitiesmentioning
confidence: 97%
“…27 In contrast, although there is no direct anatomical connection between the DLPFC and M1, 42,43 DLPFC activation decreases ipsilateral M1 corticospinal excitability. 42,44 In fact, the DLPFC is known to be involved in motor control, for example, in force control 45 and motor memory maintenance, 46 which might have contributed to the task of regulating force to 20% MVC in this study. Conversely, both M1s inhibit the other M1 via transcallosal inhibition.…”
Section: Reorganization In the Frontal Lobe And Visual Pathways Induced By Long-term Sports Activitiesmentioning
confidence: 97%